Efisiensi Usaha dan Tingkat Kesejahteraan Pengrajin Tape Ketan Di Kabupaten Kuningan - Devin Ellardo Damara; Dijan Rahajuni; Goro Binardjo (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research aims to analyze the business efficiency of the ketan tape craftsmen and to determine the level of welfare of the ketan tape craftsmen in Cibeureum District, Kuningan Regency. The number of respondents in this study were 32 people using the census method. The data collection techniques were obtained directly from respondents through observation and interviews with questionnaires.The analytical method used in this research is business efficiency analysis using R / C Ratio analysis, while for the analysis of the level of welfare by comparing the monthly income per capita of the tape ketan craftsman's family with the Regency Minimum Wage (UMK) in Kuningan RegencyThe results of this research indicate that the R / C ratio value of the ketan tape business in Cibeureum District, Kuningan Regency is 1.62. An R / C Ratio value that is greater than one means that the business is efficient and profitable and feasible to develop. Most of the ketan tape craftsmen families in Cibeureum District, Kuningan Regency can be said to be prosperous because the income per capita per month is already greater than the UMK prevailing in Kuningan Regency.